Related Risk Factors and Etiologies of Shoulder Pain after Stroke in Comprehensive Stroke Unit - Benguo WANG; Weiying ZENG; Nan YANG; Mian LIN; Yufeng HE; Feng WANG; Jingjing LU; Xianshan CAI; Yin WANG (康复学报)
Objective:To evaluate risk factors and etiologies of shoulder pain after stroke (SPAS) in comprehensive stroke unit, to further provide the basis for individualized prevention and treatment of SPAS.Methods:A total of 2 585 patients with stroke were prospectively enrolled, baseline demographic data were registered and physical examinations were evaluated, including shoulder pain, range of shoulder motion, shoulder subluxation, muscular tension, and NIHSS upper extremity muscle strength. MRI of affected shoulder was scanned and etiologies of shoulder pain were evaluated by multidisciplinary physicians. Related etiologies and risk factors were analyzed.Results:The incidence of SPAS in comprehensive stroke unit was 12.50%. Risk factors of SPAS included diabetes mellitus, recurrent stroke, limited range of shoulder motion, Brunnstrom stageⅠ-Ⅲgrade, Ashworth 3-4 grade, NIHSS upper extremity muscle strength score 3-4 points and sensory deficit. The etiologies of SPAS were complicated and the incidence rate of cuff tendinopathy was 58.64%, frozen shoulder 48.14%, rotator cuff injury 40.34%, shoulder subluxation 36.27%, shoulder-hand syndrome 26.44%, shoulder spasm 23.73%and central pain after stroke 10.85%respectively. Multiple causes of SPAS often coexisted.Conclusion:Risk factors comprise diabetes mellitus, recurrent stroke, limited range of shoulder motion, Brunnstrom stageⅠ-Ⅲgrade, Ashworth 3-4 grade, NIHSS upper extremity muscle strength score 3-4 points and sensory deficit. The etiologies of SPAS are complicated. Complicated causes of shoulder pain often interact with each other. MRI of shoulder should be scanned and multi-professional evaluation should be performed to detect the diversity and complexity of shoulder pain, which play important roles in individualized prevention and treatment.